PARTICIPANTS IN EXTRACELLULAR MATRIX DESTRUCTION AS PREDICTORS OF RECURRENCE OF FIBROMATOUS NODES GROWTH - Николаева, Мария Геннадьевна; Тимченко, Марина Алексеевна; Хорева, Лариса Александровна; Скрыльник, Александра Юрьевна (Mother and Baby in Kuzbass, 2025)
The aim of the research – determination of the role of participants in the destruction of the extracellular matrix in the pathogenesis of relapse of myomatous node growth after previously performed uterine artery embolization. Materials and methods. A prospective cohort study including 60 women who had previously undergone uterine artery embolization (UAE) for symptomatic uterine fibroids. The main group (n = 30) included patients with recurrent fibroid growth requiring medical care, and the observation group (n = 30) included patients with no clinical or ultrasound signs of disease recurrence not earlier than 36 months after UAE. All patients underwent testing for markers of extracellular matrix destruction, namely tissue plasminogen activator (t-PA), plasminogen activator inhibitor type 1 (PAI-1), urokinase plasminogen activator (u-PA), metalloprotease-1 (MMP-1), and metalloprotease-3 (MMP-3). Results. In case of relapse of myomatous node growth, a statistically significant increase is observed in the peripheral blood plasma: t-PA activity by 8.2 times (p = 0.0003), u-PA concentration and activity by 4.1 times (p < 0.0001) and 23.6 times (p < 0.0001), respectively, as well as the level of MPP-1 by 1.5 times (p = 0.0434). The threshold values and prognostic ability of the tests were determined and were as follows: t-PA activity > 1.35 U/ml (at Se = 71.4% and Sp = 100%), activity > 0.07 U/ml (at Se = 100% and Sp = 92%) and u-PA concentration > 0.33 ng/ml (at Se = 100% and Sp = 88%), MPP-1 concentration > 4567 ng/ml (at Se = 100% and Sp = 32%). Conclusion. The high prognostic ability of the tests suggests the possibility of studying fibrinolysis activators before making a decision on surgical tactics, and, possibly, considering the issue of anti-relapse therapy tactics in the future.